Acne and active patients - Pleacher, M. D.; Dexter, W. W. (The Physician and Sportsmedicine, 2005)
Acne vulgaris is a common skin condition that affects many athletes. Accurate diagnosis of the type and severity of acne lesions will help direct appropriate therapeutic interventions. Medications, including topical retinoids, topical antibiotics, oral antibiotics, and oral retinoids, are effective in treating acne. Side effects of acne therapy are common and generally mild, but athletes may require special counseling to minimize adverse effects of acne therapy. Treating acne may be challenging for both patient and physician, but with patience and perseverance, an appropriate treatment plan can provide dramatic improvements in the skin, emotional well-being, and social and athletic functioning.